(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The article is of theoretical-empirical nature. The main subject of the analysis were the conditions of socio-economic development in selected areas such as: demographic, economic, social and technical potential. The particular aim of this article was the diagnosis of socio-economic development conditions in main regions in Poland. The years 2007-2013, a period of global economic crisis were the time horizon of the analysis. In the theoretical part, the source of information was the literature on the issues of regional development. The Central Data Bank of the Central Statistical Office has been used as a source of data.